Biocontrol enemies have stronger effects than non-biocontrol enemies on insect prey - Peter Stiling; Marc J. Lajeunesse (BioControl, 2026)

Biocontrol insects have stronger effects than non-biocontrol insects on plants - Peter Stiling; Marc J. Lajeunesse (BioControl, 2025)

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Gopher tortoise herbivory increases plant species richness and diversity - Jason C. Richardson; Peter Stiling (Plant Ecology, 2019)

Release from herbivory does not confer invasion success for Eugenia uniflora in Florida - Kerry Bohl Stricker; Peter Stiling (Oecologia, 2014)

Seedlings of the introduced invasive shrub Eugenia uniflora (Myrtaceae) outperform those of its native and introduced non-invasive congeners in Florida - Kerry Bohl Stricker; Peter Stiling (Biological Invasions, 2013)

Effects of Cactoblastis cactorum on the survival and growth of North American Opuntia - Heather Jezorek; Amanda J. Baker; Peter Stiling (Biological Invasions, 2012)

Herbivory by an introduced Asian weevil negatively affects population growth of an invasive Brazilian shrub in Florida - Kerry Bohl Stricker; Peter Stiling (Ecology, 2012)
The enemy release hypothesis (ERH) is often cited to explain why some plants successfully invade natural communities while others do not. This hypothesis maintains that plant populations are regulated by coevolved enemies in their native range but are relieved of this pressure where their enemies have not been co‐introduced. Some studies have shown that invasive plants sustain lower levels of herbivore damage when compared to native species, but how damage affects fitness and population dynamics remains unclear. We used a system of co‐occurring native and invasive Eugenia congeners in south Florida (USA) to experimentally test the ERH, addressing deficiencies in our understanding of the role of natural enemies in plant invasion at the population level. Insecticide was used to experimentally exclude insect herbivores from invasive Eugenia uniflora and its native co‐occurring congeners in the field for two years. Herbivore damage, plant growth, survival, and population growth rates for the three species were then compared for control and insecticide‐treated plants. Our results contradict the ERH, indicating that E. uniflora sustains more herbivore damage than its native congeners and that this damage negatively impacts stem height, survival, and population growth. In addition, most damage to E. uniflora , a native of Brazil, is carried out by Myllocerus undatus , a recently introduced weevil from Sri Lanka, and M. undatus attacks a significantly greater proportion of E. uniflora leaves than those of its native congeners. This interaction is particularly interesting because M. undatus and E. uniflora share no coevolutionary history, having arisen on two separate continents and come into contact on a third. Our study is the first to document negative population‐level effects for an invasive plant as a result of the introduction of a novel herbivore. Such inhibitory interactions are likely to become more prevalent as suites of previously noninteracting species continue to accumulate and new communities assemble worldwide.

Selecting for Tolerance against Pathogens and Herbivores to Enhance Success of Reintroduction and Translocation - MATTHEW D. VENESKY; JOSEPH R. MENDELSON III; BRITTANY F. SEARS; PETER STILING; JASON R. ROHR (Conservation Biology, 2012)
Some species have insufficient defenses against climate change, emerging infectious diseases, and non‐native species because they have not been exposed to these factors over their evolutionary history, and this can decrease their likelihood of persistence. Captive breeding programs are sometimes used to reintroduce individuals back into the wild; however, successful captive breeding and reintroduction can be difficult because species or populations often cannot coexist with non‐native pathogens and herbivores without artificial selection. In captive breeding programs, breeders can select for host defenses that prevent or reduce pathogen or herbivore burden (i.e., resistance) or traits that limit the effects of parasitism or herbivory on host fitness (i.e., tolerance). We propose that selection for host tolerance may enhance the success of reintroduction or translocation because tolerant hosts generally have neutral effects on introduced pathogens and herbivores. The release of resistant hosts would have detrimental effects on their natural enemies, promoting rapid evolution to circumvent the host resistance that may reduce the long‐term probability of persistence of the reintroduced or translocated species. We examined 2 case studies, one on the pathogenic amphibian chytrid fungus ( Batrachochytrium dendrobatidis [Bd]) and the other on the herbivorous cactus moth ( Cactoblastis cactorum) in the United States, where it is not native. In each case study, we provide recommendations for how captive breeders and managers could go about selecting for host tolerance. Selecting for tolerance may offer a promising tool to rescue hosts species from invasive natural enemies as well as new natural enemies associated with climate change‐induced range shifts.

Ant predation on an invasive herbivore: can an extrafloral nectar-producing plant provide associational resistance to Opuntia individuals? - Heather Jezorek; Peter Stiling; James Carpenter (Biological Invasions, 2011)

Similar responses of insect herbivores to leaf fluctuating asymmetry - Tatiana Cornelissen; Peter Stiling (Arthropod-Plant Interactions, 2011)

Seeing the forest for the trees: long‐term exposure to elevated CO 2 increases some herbivore densities - PETER STILING; DANIEL MOON; ANTHONY ROSSI; BRUCE A. HUNGATE; BERT DRAKE (Global Change Biology, 2009)
The effects of elevated CO 2 on plant growth and insect herbivory have been frequently investigated over the past 20 years. Most studies have shown an increase in plant growth, a decrease in plant nitrogen concentration, an increase in plant secondary metabolites and a decrease in herbivory. However, such studies have generally overlooked the fact that increases in plant production could cause increases of herbivores per unit area of habitat. Our study investigated leaf production, herbivory levels and herbivore abundance per unit area of leaf litter in a scrub‐oak system at Kennedy Space Center, Florida, under conditions of ambient and elevated CO 2 , over an 11‐year period, from 1996 to 2007. In every year, herbivory, that is leafminer and leaftier abundance per 200 leaves, was lower under elevated CO 2 than ambient CO 2 for each of three species of oaks, Quercus myrtifolia, Quercus chapmanii and Quercus geminata . However, leaf litter production per 0.1143 m 2 was greater under elevated CO 2 than ambient CO 2 for Q. myrtifolia and Q. chapmanii , and this difference increased over the 11 years of the study. Leaf production of Q. geminata under elevated CO 2 did not increase. Leafminer densities per 0.1143 m 2 of litterfall for Q. myrtifolia and Q. chapmanii were initially lower under elevated CO 2 . However, shortly after canopy closure in 2001, leafminer densities per 0.1143 m 2 of litter fall became higher under elevated CO 2 and remained higher for the remainder of the experiment. Leaftier densities per 0.1143 m 2 were also higher under elevated CO 2 for Q. myrtifolia and Q. chapmanii over the last 6 years of the experiment. There were no differences in leafminer or leaftier densities per 0.1143 m 2 of litter for Q. geminata . These results show three phenomena. First, they show that elevated CO 2 decreases herbivory on all oak species in the Florida scrub‐oak system. Second, despite lower numbers of herbivores per 200 leaves in elevated CO 2 , increased leaf production resulted in higher herbivore densities per unit area of leaf litter for two oak species. Third, they corroborate other studies which suggest that the effects of elevated CO 2 on herbivores are species specific, meaning they depend on the particular plant species involved. Two oak species showed increases in leaf production and herbivore densities per 0.1143 m 2 in elevated CO 2 over time while another oak species did not. Our results point to a future world of elevated CO 2 where, despite lower plant herbivory, some insect herbivores may become more common.

Comparing the effects of the exotic cactus-feeding moth, Cactoblastis cactorum (Berg) (Lepidoptera: Pyralidae) and the native cactus-feeding moth, Melitara prodenialis (Walker) (Lepidoptera: Pyralidae) on two species of Florida Opuntia - Amanda J. Baker; Peter Stiling (Biological Invasions, 2009)

Effects of aphid-tending Argentine ants, nitrogen enrichment and early-season herbivory on insects hosted by a coastal shrub - Laura Altfeld; Peter Stiling (Biological Invasions, 2009)

Does enemy release matter for invasive plants? evidence from a comparison of insect herbivore damage among invasive, non-invasive and native congeners - Hong Liu; Peter Stiling; Robert W. Pemberton (Biological Invasions, 2007)

How does elevated carbon dioxide (CO 2 ) affect plant–herbivore interactions? A field experiment and meta‐analysis of CO 2 ‐mediated changes on plant chemistry and herbivore performance - PETER STILING; TATIANA CORNELISSEN (Global Change Biology, 2007)
First, we report the results of the longest‐known field study (9 years) to examine the effects of elevated carbon dioxide (CO 2 ) on leaf miner densities in a scrub‐oak community at Kennedy Space Center, Florida. Here, the densities of all leaf miner species (6) on all host species (3) were lower in every year in elevated CO 2 than they were in ambient CO 2 . Second, meta‐analyses were used to review the effects of elevated CO 2 on both plants ( n =59 studies) and herbivores ( n =75 studies). The log of the response ratio was chosen as the metric to calculate effect sizes. Results showed that elevated CO 2 significantly decreased herbivore abundance (−21.6%), increased relative consumption rates (+16.5%), development time (+3.87%) and total consumption (+9.2%), and significantly decreased relative growth rate (−8.3%), conversion efficiency (−19.9%) and pupal weight (−5.03%). No significant differences were observed among herbivore guilds. Host plants growing under enriched CO 2 environments exhibited significantly larger biomass (+38.4%), increased C/N ratio (+26.57%), and decreased nitrogen concentration (−16.4%), as well as increased concentrations of tannins (+29.9%) and other phenolics. Effects of changes on plant primary and secondary chemistry due to elevated CO 2 and consequences for herbivore growth and development are discussed.

Testing the enemy release hypothesis: a review and meta-analysis - Hong Liu; Peter Stiling (Biological Invasions, 2006)

Elevated CO 2 increases the long‐term decomposition rate of Quercus myrtifolia leaf litter - MYRA C. HALL; PETER STILING; DANIEL C. MOON; BERT G. DRAKE; MARK D. HUNTER (Global Change Biology, 2006)
Decomposition of Quercus myrtifolia leaf litter in a Florida scrub oak community was followed for 3 years in two separate experiments. In the first experiment, we examined the effects CO 2 and herbivore damage on litter quality and subsequent decomposition. Undamaged, chewed and mined litter generated under ambient and elevated (ambient+350 ppm V) CO 2 was allowed to decompose under ambient conditions for 3 years. Initial litter chemistry indicated that CO 2 levels had minor effects on litter quality. Litter damaged by leaf miners had higher initial concentrations of condensed tannins and nitrogen (N) and lower concentrations of hemicellulose and C : N ratios compared with undamaged and chewed litter. Despite variation in litter quality associated with CO 2 , herbivory, and their interaction, there was no subsequent effect on rates of decomposition under ambient atmospheric conditions. In the second experiment, we examined the effects of source (ambient and elevated) of litter and decomposition site (ambient and elevated) on litter decomposition and N dynamics. Litter was not separated by damage type. The litter from both elevated and ambient CO 2 was then decomposed in both elevated and ambient CO 2 chambers. Initial litter chemistry indicated that concentrations of carbon (C), hemicellulose, and lignin were higher in litter from elevated than ambient CO 2 chambers. Despite differences in C and fiber concentrations, litter from ambient and elevated CO 2 decomposed at comparable rates. However, the atmosphere in which the decomposition took place resulted in significant differences in rates of decomposition. Litter decomposing under elevated CO 2 decomposed more rapidly than litter under ambient CO 2 , and exhibited higher rates of mineral N accumulation. The results suggest that the atmospheric conditions during the decomposition process have a greater impact on rates of decomposition and N cycling than do the atmospheric conditions under which the foliage was produced.

Effects of Elevated CO2 and Herbivore Damage on Litter Quality in a Scrub Oak Ecosystem - Myra C. Hall; Peter Stiling; Bruce A. Hungate; Bert G. Drake; Mark D. Hunter (Journal of Chemical Ecology, 2005)

Effects of elevated CO2 on foliar quality and herbivore damage in a scrub oak ecosystem - Myra C. Hall; Peter Stiling; Daniel C. Moon; Bert G. Drake; Mark D. Hunter (Journal of Chemical Ecology, 2005)

Quality or quantity: the direct and indirect effects of host plants on herbivores and their natural enemies - Peter Stiling; Daniel C. Moon (Oecologia, 2005)

Perfect is best: low leaf fluctuating asymmetry reduces herbivory by leaf miners - Tatiana Cornelissen; Peter Stiling (Oecologia, 2005)

Induced Defensive Response of Myrtle Oak to Foliar Insect Herbivory in Ambient and Elevated Co2 - Anthony M. Rossi; Peter Stiling; Daniel C. Moon; Maria V. Cattell; Bert G. Drake (Journal of Chemical Ecology, 2004)

Biological Control not on Target - Peter Stiling (Biological Invasions, 2004)

Differential effects of elevated CO 2 on acorn density, weight, germination, and predation among three oak species in a scrub‐oak forest - Peter Stiling; Daniel Moon; Graham Hymus; Bert Drake (Global Change Biology, 2004)
Much research on the effects of elevated CO 2 on forest trees has focused on quantitative changes in photosynthesis, secondary chemistry, and plant biomass. However, plant fitness responses to rising CO 2 should also include quantitative measures of reproduction, since most forest systems are recruitment limited. Until now, it has proved very difficult to grow forest trees to sexual maturity in a CO 2 ‐enriched environment. This paper is the first of its kind to address the effects of elevated CO 2 on the reproduction of hardwood trees in a natural forest. Beginning in 1996, scrub‐oak vegetation, predominantly three species of scrub‐oaks, Quercus myrtifolia , Q . chapmanii , and Q . geminata , were grown inside eight chambers with elevated CO 2 (704 parts per million (ppm)) and eight with ambient CO 2 (379 ppm) at Kennedy Space Center, Florida. In elevated CO 2 , acorn production increased significantly for the dominant species Q . myrtifolia and for Q . chapmanii , but it did not increase for the subdominant, Q . geminata . Acorn weight, germination rate, and predation by weevils were unaffected by CO 2 . Thus, recruitment of some forest tree species into the Florida scrub‐oak community is likely to be accelerated in an atmosphere of increased CO 2 . However, because the acceleration of recruitment differs among species, over the long term, Q. myrtifolia and Q. chapmanii will be favored over Q. geminata and this is likely to change patterns of species diversity.

The Double‐Edged Sword of Biological Control in Conservation and Restoration - SVATA M. LOUDA; PETER STILING (Conservation Biology, 2004)

Elevated CO 2 decreases leaf fluctuating asymmetry and herbivory by leaf miners on two oak species - Tatiana Cornelissen; Peter Stiling; Bert Drake (Global Change Biology, 2004)
Fluctuating asymmetry (FA) represents small, random variation from symmetry in otherwise bilaterally symmetrical characters. Significant increases in FA have been found for several species of plants and animals in response to various stresses, including environmental and genetic factors. In this study, we investigated the effects of elevated CO 2 on leaf symmetry of two oak species, Quercus geminata and Q. myrtifolia , and the responses of three species of leaf miners and one gall‐making species to random variation in leaf morphology. Leaf FA decreased with an increase in CO 2 concentration. There were fewer asymmetric leaves and lower levels of asymmetry on leaf width and leaf area on elevated CO 2 compared with ambient CO 2 . Leaf miners responded to leaf asymmetry, attacking asymmetric leaves more frequently than expected by chance alone. Differences in secondary chemistry and nitrogen (N) content between symmetric and asymmetric leaves may be responsible for these results due to lower levels of tannins and higher levels of N found on asymmetric leaves of Q. myrtifolia and Q. geminata .

The influence of species identity and herbivore feeding mode on top-down and bottom-up effects in a salt marsh system - Daniel C. Moon; Peter Stiling (Oecologia, 2002)

Seasonal variability in the effect of elevated CO 2 on ecosystem leaf area index in a scrub‐oak ecosystem - Graham J. Hymus; Jean‐Yves Pontailler; Jiahong Li; Peter Stiling; C. Ross Hinkle; Bert G. Drake (Global Change Biology, 2002)
We report effects of elevated atmospheric CO 2 concentration ( C a ) on leaf area index (LAI) of a Florida scrub‐oak ecosystem, which had regenerated after fire for between three and five years in open‐top chambers (OTCs) and was yet to reach canopy closure. LAI was measured using four nondestructive methods, calibrated and tested in experiments performed in calibration plots near the OTCs. The four methods were: PAR transmission through the canopy, normalized difference vegetation index (NDVI), hemispherical photography, and allometric relationships between plant stem diameter and plant leaf area. Calibration experiments showed: (1) Leaf area index could be accurately determined from either PAR transmission through the canopy or hemispherical photography. For LAI determined from PAR transmission through the canopy, ecosystem light extinction coefficient ( k ) varied with season and was best described as a function of PAR transmission through the canopy. (2) A negative exponential function described the relationship between NDVI and LAI; (3) Allometric relationships overestimated LAI. Throughout the two years of this study, LAI was always higher in elevated C a , rising from, 20% during winter, to 55% during summer. This seasonality was driven by a more rapid development of leaf area during the spring and a relatively greater loss of leaf area during the winter, in elevated C a . For this scrub‐oak ecosystem prior to canopy closure, increased leaf area was an indirect mechanism by which ecosystem C uptake and canopy N content were increased in elevated C a . In addition, increased LAI decreased potential reductions in canopy transpiration from decreases in stomatal conductance in elevated C a . These findings have important implications for biogeochemical cycles of C, N and H 2 O in woody ecosystems regenerating from disturbance in elevated C a .

Potential Non-target Effects of a Biological Control Agent, Prickly Pear Moth, Cactoblastis cactorum (Berg) (Lepidoptera: Pyralidae), in North America, and Possible Management Actions - Peter Stiling (Biological Invasions, 2002)

Elevated atmospheric CO 2 lowers herbivore abundance, but increases leaf abscission rates - Peter Stiling; Maria Cattell; Daniel C. Moon; Anthony Rossi; Bruce A. Hungate; Graham Hymus; Bert Drake (Global Change Biology, 2002)
Increased levels of atmospheric carbon dioxide (CO 2 ) are likely to affect the trophic relationships that exist between plants, their herbivores and the herbivores' natural enemies. This study takes advantage of an open‐top CO 2 fertilization experiment in a Florida scrub oak community at Kennedy Space Center, Florida, consisting of eight chambers supplied with ambient CO 2 (360 ppm) and eight chambers supplied with elevated CO 2 (710 ppm). We examined the effects of elevated CO 2 on herbivore densities and levels of leaf consumption, rates of herbivore attack by natural enemies and effects on leaf abscission. Cumulative levels of herbivores and herbivore damage were significantly lower in elevated CO 2 than in ambient CO 2 . This may be because leaf nitrogen levels are lower in elevated CO 2 . More herbivores die of host plant‐induced death in elevated CO 2 than in ambient CO 2 . Attack rates of herbivores by parasitoids are also higher in elevated CO 2 , possibly because herbivores need to feed for a longer time in order to accrue sufficient nitrogen (N), thus exposing themselves longer to natural enemies. Insect herbivores cause an increase in abscission rates of leaves throughout the year. Because of the lower insect density in elevated CO 2 , we thought, abscission rates would be lower in these chambers. However, abscission rates were significantly higher in elevated CO 2 . Thus, the direct effects of elevated CO 2 on abscission are greater than the indirect effects on abscission mediated via lower insect densities. A consequence of increased leaf abscission in elevated CO 2 is that nutrient deposition rates to the soil surface are accelerated.

Experimental tests of trophic dynamics: taking a closer look - Daniel C. Moon; Peter Stiling; Maria V. Cattell (Oecologia, 1999)

The influence of salt and nitrogen on herbivore abundance: direct and indirect effects - Todd I. Bowdish; Peter Stiling (Oecologia, 1998)